SITC perspective: leveraging patient enrichment biomarkers to accelerate early phase IO drug development - James L Gulley; Leisha A Emens; Patrick Hwu; Carlo B Bifulco; Pamela S Ohashi; Christine Moussion; David Feltquate (Journal for ImmunoTherapy of Cancer, 2025)
Cancer immunotherapy (IO) enables patients to live well with cancer for many years, or even be cured. Several investigational IO agents recently failed in early-phase or late-phase trials, leading some to doubt the future of IO. Patient heterogeneity (eg, tumor characteristics, treatment history) increases the risk that a clinically active IO drug might be discarded. Enriching enrollment for patients with biomarkers hypothesized to reflect a higher probability of clinical benefit across clinical development should mitigate this risk. The Society for Immunotherapy of Cancer convened diverse IO stakeholders to discuss leveraging biomarkers at the earliest stages of drug development to accelerate the delivery of innovative IO agents to patients. This group developed a framework based on a biomarker-based enrichment strategy in early trials that evolves into the development of more precise predictive biomarkers in late phase trials. This framework integrates mechanistic insights related to the drug and its impact on the tumor microenvironment derived from preclinical data, digital pathology, exploratory multiomics, and artificial intelligence that are continuously refined through both adaptive and randomized clinical trials. Biomarker-based enrichment in early clinical development should de-risk late-stage trials, ultimately expanding the portfolio of innovative IO drugs available to patients.